2010
DOI: 10.1016/j.seizure.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Does a preference for fatty foods prior to commencing treatment with the ketogenic diet predict the efficacy of this diet?

Abstract: The ketogenic diet can be effective in children who suffer from drug-resistant epilepsy. However, it is still hard to predict how large an effect this diet will have for an individual child. Previous data suggests a high-fat food preference is more likely in those with epilepsy, as assessed by in-person forced-choice design. The aim of this study is to examine whether a partiality to fatty foods prior to commencing the ketogenic diet can be used as a predictive factor for the efficacy of this diet in children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…Although tentative, these results provide initial support for the predictive value of fat preference for responsiveness to dietary intervention. The modest correlations between fat preference and diet efficacy obtained in this study stand in contrast to the null findings of Dekker et al 8 It seems likely that the difference in outcomes is a result of the methods used to assess preference. Further study utilizing direct measurement of preference is warranted.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although tentative, these results provide initial support for the predictive value of fat preference for responsiveness to dietary intervention. The modest correlations between fat preference and diet efficacy obtained in this study stand in contrast to the null findings of Dekker et al 8 It seems likely that the difference in outcomes is a result of the methods used to assess preference. Further study utilizing direct measurement of preference is warranted.…”
Section: Discussioncontrasting
confidence: 99%
“…Dekker et al 8 examined the preferences of 43 children and did not identify a significant correlation between fat preferences and ketogenic diet efficacy. However, these researchers utilized a retrospective, non-validated questionnaire completed by the children's parents (at times recollecting up to 5 years in the past) in addition to review of a parent-report food log completed prior to diet commencement, measuring consumption and not preference specifically.…”
Section: Introductionmentioning
confidence: 99%
“…Research in paediatric groups has shown that dietary preferences have mixed impact on the ketogenic diet. For example, while existing preference for high-fat food types is not considered to influence adherence [62], overall dietary preferences are one of the strongest drivers of discontinuation [63]. There remains work to be done to better understand the role of preferences in adults with bipolar disorder, who can experience concomitant challenges of disordered eating.…”
Section: Resultsmentioning
confidence: 99%